Pro‐Peptide‐Reinforced, Mucus‐Penetrating Pulmonary siRNA Delivery Mitigates Cytokine Storm in Pneumonia. (19th March 2021) - Yang, Jiandong; Duan, Shanzhou; Ye, Huan; Ge, Chenglong; Piao, Chunxian; Chen, Yongbing; Lee, Minhyung; Yin, Lichen
Abstract: Pulmonary delivery of anti‐inflammatory siRNA holds great potential in mitigating the cytokine storm during severe pneumonia. However, commonly utilized polycationic siRNA delivery vehicles can hardly penetrate the mucus barrier, thus greatly hurdling their therapeutic efficacy. Herein, TNF‐α siRNA (siTNF‐α) delivery nanocomplexes (NCs) are engineered with mucus/cytomembrane dual‐penetration capabilities, realized via surface‐coating of NCs with RC, an inflammation‐sheddable, charge‐reversal pro‐peptide of RAGE‐binding peptide (RBP). RC‐coated dendritic poly‐L ‐lysine/siTNF‐α (DsT) NCs possess negative surface charges, and can thus efficiently penetrate the mucus layer after intratracheal administration. In the inflamed alveolar space with mild acidity, RC recovers to the cationic RBP and shed off, re‐exposing the DsT NCs that efficiently transfect the alveolar macrophages and provokes TNF‐α silencing. Thus, siTNF‐α and RBP cooperatively alleviate the uncontrolled inflammation during acute lung injury. This study renders a unique approach for mediating trans‐mucus nucleic acid delivery, and will find promising utilities for the treatment of severe pneumonia. Abstract : Mucus‐penetrating nanocomplexes for pulmonary TNF‐α siRNA delivery are developed via surface‐coating with RC, a charge‐reversal pro‐peptide that generates negative surface charges. In the inflamed alveolar space, RC is reactivated and sheds off to expose the cationic inner core, facilitating siRNA transfection in macrophages. Finally, re‐activated RC (RAGE‐binding peptide) and TNF‐α siRNA cooperate to mitigate the cytokine storm in severe pneumonia.